Changes in Coagulation following Brain Injury - Maegele, Marc; Aversa, John; Marsee, Mathew K.; McCauley, Ross; Chitta, Swetha Hanuma; Vyakaranam, Sudhir; Walsh, Mark (Seminars in Thrombosis and Hemostasis, 2020)
Traumatic brain injury (TBI) is a worldwide public health concern due to increasing mortality, affecting around 10 million patients per year. A wide variety of clinical presentations are a function of the magnitude of injury and the anatomical perturbation of the brain parenchyma, supporting structures, and cerebral vasculature, with subsequent alteration of the blood–brain barrier. These disturbances correspond with the evolution of intracerebral hemorrhage and clinical outcomes. The associated hemostatic alterations associated with TBI are caused by the disruption of the delicate balance between bleeding and thrombosis formation, which can exacerbate initial injury. TBI-associated coagulopathy is a function of a cross-talk between coagulation and inflammation, with varying influences on the immunomodulation and regulation of coagulation that occur on platelets and the endothelium of injured TBI patients. In addition to the severity of initial injury, the following factors modulate the hemocoagulative response to TBI: time from the onset of injury to treatment, age, gender, catecholamine secretion, platelet dysfunction, endotheliopathy, premorbid anticoagulation, fibrinolysis, tissue factor, and activated protein C contribution. All these entities are intertwined and influence the pathologic evolution of TBI. These factors have implications for therapeutic options such as the choice of blood components for transfusion and hemostatic agents such as tranexamic acid. Monitoring hemostatic changes of TBI patients requires an understanding of these interactions between immunology and coagulation, which can be discerned by point-of-care viscoelastic testing with specific limitations. This review considers the implications of these interrelated influences on the evaluation of coagulopathy in TBI.
Keywords: traumatic brain injury; coagulopathy; platelet dysfunction; endotheliopathy; intracerebral hemorrhage; tranexamic acid; thromboelastography; rotational thromboelastometry